To the question of hydrolates - Garkava, K.G.; Bykova, A.V. (Problems of Environmental Biotechnology, 2021)
Hydrolates are substances, obtained as a result of steam distillation of plant material and have a wide range of water-soluble components and microelements of essential oils. Due to their properties, they can effectively influence the function of vital systems in the body.